On Some Geometrical Properties of Generalized Modular Spaces of Cesaro Type Defined by Weighted Means - Simsek, Necip; Karakaya, Vatan (SPRINGER INTERNATIONAL PUBLISHING AG, 2009)
The main purpose of this paper is to introduce modular structure of the sequence space defined by Altay and Basar (2007), and to study Kadec-Klee (H) and uniform Opial properties of this sequence space on Kothe sequence spaces. Copyright (C) 2009 N. Simsek and V. Karakaya.
Keywords: NONEXPANSIVE-MAPPINGS; SEQUENCE-SPACES; Mathematics